ENTREPRENEURSHIP AND MARGINAL ANALYSIS OF INVESTMENTS - Gomero Gonzales, Nicko Alberto (2011)
It requires companies with solid skills to achieve sustainable positioning in global markets. The opening of markets requiresthe modernization not only large corporationsbut also small enterprises, which as we know it are becoming productive arms ofcountries, the modernization not only be technological, but also of knowledge, concepts of ideas, that is why in this article presents a theoretical model of corporate governancefor making investmentdecisions, which is called “Marginal Analysis of Investments’financial tool that leads to make the best investment decision under two mutually exclusive alternatives. If an entrepreneur has a going concern and would like to injectliquidity through investments, which would have to determine the added value that would generate this decision, if positive, the value of the business will experience a major improvement, a result that is obtained with the Marginal Model Investment.